The superiority of antidepressant medication to cognitive behavior therapy in melancholic depressed patients: a 12‐week single‐blind randomized study. (14th December 2012) - Parker, G.; Blanch, B.; Paterson, A.; Hadzi‐Pavlovic, D.; Sheppard, E.; Manicavasagar, V.; Synnott, H.; Graham, R. K.; Friend, P.; Gilfillan, D.; Perich, T.
<x xml:space="preserve">Abstract</x> Objective To pursue the previously long‐standing but formally untested clinical view that melancholia is preferentially responsive to antidepressant medication in comparison with psychotherapy [specifically Cognitive Behavior Therapy (CBT)]. Second, to determine whether a broader action antidepressant medication sequencing regimen is superior to a Selective Serotonin Reuptake Inhibitor (SSRI) alone. Method We sought to recruit a large sample of participants with melancholic depression for a 12‐week trial but inclusion criteria compromised recruitment and testing the second hypothesis. The first hypothesis was evaluated by comparing 18 participants receiving antidepressant medication to 11 receiving CBT. Primary study measures were the Hamilton Rating Scale for Depression (HAM‐D) and the Hamilton Endogenous Subscale (HES), rated blindly, while several secondary measures also evaluated outcome. Results Participants receiving medication had a superior 12‐week outcome to those receiving CBT, with significant differences present on primary measures as early as 4 weeks. At trial conclusion, the percentage improvement in HAM‐D scores was 61.1% vs. 34.4%, respectively [Number Needed to Treat (NNT) = 3.7] and with those in receipt of medication returning non‐significantly higher HAM‐D responder (66.6% vs. 36.4%, NNT = 2.8) and remission (66.7% vs. 45.4%, NNT = 4.7) rates. Conclusion As the sample size was small and participants evidenced only moderate levels of depression severity, the study risked being underpowered and idiosyncratic. Despite the small sample, the superiority of antidepressant medication to CBT in those with a melancholic depression was distinctive in this pilot study.